PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KABUPATEN TOJO UNA-UNA - Muhtar, Muhtar (Katalogis, 2017)
The study defines leadership style and motivation as independent variables and performance as dependent variable. Leadership style in this study refers to three indicators namely: 1) directing subordinates in performing jobs; 2) participating with subordinates; 3) trusting subordinates. Motivation refers to 5 indicators that are: 1) recognition from counterparts; 2) recognition from leaders; 3) recognition from organization; 4) opportunities for promotion; 5) initiating good performance. Performance refers to 7 indicators: 1) loyalty; 2) spirit; 3) work consistency; 4) honesty; 5) work clarity; 6) teamwork; 7) capability. The research aims to determine and analyze simultaneous influence of leadership style and motivation on officials’ performance in The Department of Transportation, Communication, and Informatics of Tojo Una-Una District. Tool analysis is multiple linear regressions. Based on the results, it is found that leadership style and motivation have significant influence on officials’ performance, both simultaneosuly and partially in The Department of Transportation, Communication, and Informatics of Tojo Una-Una District.